Libraries in the Press of Occupied Istanbul: Collective Memory and National Identity - Aldırmaz, Yaşar (Information World, 2025)
Throughout history, libraries have played a central role in shaping cultural identity and preserving collective memory, in addition to being repositories of knowledge. The occupation of Istanbul following the Armistice of Mudros brought the issue of preserving the Ottoman intellectual heritage to the forefront. News published in the press reflected the public’s will to protect cultural heritage, as well as the physical and administrative problems of libraries. The press treated libraries as institutions of strategic importance in preserving cultural independence and national identity. This situation shows that libraries were seen as part of an intellectual and cultural resistance, beyond their physical existence. Within the framework of Michel Foucault’s power-knowledge analysis and Pierre Bourdieu’s cultural capital concept, libraries stand out as spaces where knowledge is controlled, reproduced, and shaped by social power relations. In this study, by examining the necessity of centralizing waqf libraries under a single system in occupied Istanbul and how the individual intellectual efforts of figures such as Ali Emiri Efendi and Izmirli İsmail Hakkı Bey were received, it is revealed how cultural memory was shaped and how knowledge was managed within power relations. The findings show that during the occupation, institutions of knowledge and memory were positioned not just as physical entities but as part of social and political struggles. By revealing the effects of institutional weakness in the Ottoman bureaucracy on the preservation of cultural heritage, this study provides a strong foundation for future comparative research on the preservation and reproduction of knowledge under extraordinary conditions such as war and occupation.